2008
DOI: 10.1038/ni.1606
|View full text |Cite
|
Sign up to set email alerts
|

Sequential control of Toll-like receptor–dependent responses by IRAK1 and IRAK2

Abstract: Members of the IRAK family of kinases mediate Toll-like receptor (TLR) signaling. Here we show that IRAK2 was essential for sustaining TLR-induced expression of genes encoding cytokines and activation of the transcription factor NF-kappaB, despite the fact that IRAK2 was dispensable for activation of the initial signaling cascades. IRAK2 was activated 'downstream' of IRAK4, like IRAK1, and TLR-induced cytokine production was abrogated in the absence of both IRAK1 and IRAK2. Whereas the kinase activity of IRAK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
350
4
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 380 publications
(370 citation statements)
references
References 48 publications
14
350
4
2
Order By: Relevance
“…We were unable to test leukocyte subsets or responses to agonists of other members of the TLR (e.g., TLR5 and TLR9) and IL-1R (e.g., IL-18R and IL-33R) families. Overall, our results, somewhat at odds with the data obtained for mutant mice (5,23,36) (SI Appendix, Table S2), suggest that human IRAK-1 is largely redundant downstream from both TLRs and IL-1R in mononuclear blood cells and downstream from IL-1R in fibroblasts, whereas it plays an essential role, at least downstream from TLR2/6, TLR4, TLR7, and TLR8, in fibroblasts and EBV-B cells.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…We were unable to test leukocyte subsets or responses to agonists of other members of the TLR (e.g., TLR5 and TLR9) and IL-1R (e.g., IL-18R and IL-33R) families. Overall, our results, somewhat at odds with the data obtained for mutant mice (5,23,36) (SI Appendix, Table S2), suggest that human IRAK-1 is largely redundant downstream from both TLRs and IL-1R in mononuclear blood cells and downstream from IL-1R in fibroblasts, whereas it plays an essential role, at least downstream from TLR2/6, TLR4, TLR7, and TLR8, in fibroblasts and EBV-B cells.…”
Section: Discussioncontrasting
confidence: 56%
“…By contrast, the patient's PBMCs responded normally to all TLR (TLR1/2, TLR2/6, TLR4, TLR7, and TLR8) agonists tested and to IL-1β (in terms of the production of many cytokines), whereas neither IRAK-4-nor MyD88-deficient PBMCs responded to any of these TLR (except for some residual TLR4 signaling, presumably via TRIF) and IL-1R (SI Appendix, Table S1) agonists. By contrast, Irak1-deficient MEFs displayed strong but incomplete impairment of the response to both TLRs (TLR2 and TLR4) (23) and IL-1Rs (5,23,36). This result is at odds with the almost complete abolition of responses to TLR2/6 and TLR4 agonists, and the preserved response to IL-1β observed in human IRAK-1-deficient fibroblasts.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Genetic proof of the role of IRAK1 and IRAK2 as well as IRAK4 and TRAF6 in IL-1R1/IL-18R and TLR signaling was reported shortly after by several groups (23)(24)(25)(26)(27). Subsequent studies revealed that IRAK2 was activated downstream of IRAK4, and IRAK1 and IRAK2 acted sequentially in TLR signaling (28).…”
Section: Myd88: a Critical Adaptor Protein In Innate Immunity Signal mentioning
confidence: 99%